Development of a potential optical thermometric material through photoluminescence of Pr3+ in La2MgTiO6. Issue 41 (28th September 2017) - Shi, Rui; Lin, Litian; Dorenbos, Pieter; Liang, Hongbin
Abstract : Systematic research indicates that Pr 3+ doped La2 MgTiO6 has application potential in the highly sensitive optical thermometry field. Abstract : In this work, we demonstrate a potential thermometric material after systematic studies on the concentration/temperature-dependent spectroscopic properties of Pr 3+ excited multiplets and of the Pr 3+ –Ti 4+ intervalence charge transfer (IVCT) state in (La1− x Pr x )2 MgTiO6 . The experimental results indicate that the electron population efficiency between the involved Pr 3+ 4f multiplets is directly governed by multi-phonon relaxation (MPR) and cross relaxation (CR), and the IVCT state provides an additional contribution to the 1 D2 luminescence. A schematic energy level diagram is proposed to illustrate the electron population pathway in Pr 3+ doped La2 MgTiO6 . The observations clarify that the dramatic thermal-quenching of 3 P0 luminescence is mainly induced by the electronic configuration crossover between the 3 P0 multiplet and the IVCT state. On the other hand, the 1 D2 luminescence possesses an excellent thermal stability in a large temperature region. These temperature sensing features of the Pr 3+ doped La2 MgTiO6 material indicate its potential application in optical thermometric techniques.